Species of the genus Ensiferella Andersson from China, with a key to world species (Diptera, Chloropidae) - Liu, Xiaoyan; Yang, Ding (Zootaxa, 2012)
The genus Ensiferella Andersson is newly recorded from China. The following two species are described as new to sci-ence: E. elongata sp. nov. and E. longispina sp. nov. The male of E. sabroskyi Nartshuk is described for the first time. Twospecies, E. kanmiyai Nartshuk and E. sabroskyi Nartshuk, are newly recorded from China. A key to the world species of genus Ensiferella is given.